Predicting phytoplankton growth and dynamics in relation to physico-chemical characteristics of water body - Sharma N.K.; Mohan D.; Rai A.K. (My University, 2025)
In recent times, frequency and severity of algal blooms has increased significantly. To control their expansion, it is essential to identify the factors responsible for blooming of waters. Nutrient over-enrichment (mainly due to anthropogenic activities) and environmental factors (including the climate change) are considered the major catalyst for onset, proliferation, and development of blooms. A eutrophic subtropical water reservoir (Durgakund Pond, Varanasi) was sampled for 2 years (2000-2002), and data were obtained on various physico-chemical factors such as temperature, dissolved oxygen, pH, phosphorus (PO4 - and other P forms), nitrogen (NO3 -, NO2 -, and NH+ 4), chloride, iron, and phytoplankton biomass in terms of chlorophyll a, total protein, and carbohydrate content. Linear regression models that developed indicated that phosphorous, nitrogen, and iron had maximal impact on phytoplankton growth. Physical factors, though vital, had an indirect effect in facilitating the interaction among various nutrients and their availability. © 2009 Springer Science+Business Media B.V.